Genetic Ablation of TASK-1 (Tandem of P Domains in a Weak Inward Rectifying K+ Channel–Related Acid-Sensitive K+ Channel-1) (K2P3.1) K+ Channels Suppresses Atrial Fibrillation and Prevents Electrical Remodeling. (September 2019) - Schmidt, Constanze; Wiedmann, Felix; Beyersdorf, Christoph; Zhao, Zhihan; El-Battrawy, Ibrahim; Lan, Huan; Szabo, Gabor; Li, Xin; Lang, Siegfried; Korkmaz-Icöz, Sevil; Rapti, Kleopatra; Jungmann, Andreas; et al.
Abstract : Background: Despite an increasing understanding of atrial fibrillation (AF) pathophysiology, translation into mechanism-based treatment options is lacking. In atrial cardiomyocytes of patients with chronic AF, expression, and function of tandem of P domains in a weak inward rectifying TASK-1 (K + channel–related acid-sensitive K + channel-1) (K2P 3.1) atrial-specific 2-pore domain potassium channels is enhanced, resulting in action potential duration shortening. TASK-1 channel inhibition prevents action potential duration shortening to maintain values observed among sinus rhythm subjects. The present preclinical study used a porcine AF model to evaluate the antiarrhythmic efficacy of TASK-1 inhibition by adeno-associated viral anti–TASK-1-siRNA (small interfering RNA) gene transfer. Methods: AF was induced in domestic pigs by atrial burst stimulation via implanted pacemakers. Adeno-associated viral vectors carrying anti–TASK-1-siRNA were injected into both atria to suppress TASK-1 channel expression. After the 14-day follow-up period, porcine cardiomyocytes were isolated from right and left atrium, followed by electrophysiological and molecular characterization. Results: AF was associated with increased TASK-1 transcript, protein and ion current levels leading to shortened action potential duration in atrial cardiomyocytes compared to sinus rhythm controls, similar to previous findings in humans. Anti–TASK-1 adeno-associated viral application significantly reduced AF burden in comparison to untreated AF pigs. Antiarrhythmic effects of anti–TASK-1-siRNA were associated with reduction of TASK-1 currents and prolongation of action potential durations in atrial cardiomyocytes to sinus rhythm values. Conclusions: Adeno-associated viral-based anti–TASK-1 gene therapy suppressed AF and corrected cellular electrophysiological remodeling in a porcine model of AF. Suppression of AF through selective reduction of TASK-1 currents represents a new option for antiarrhythmic therapy. Abstract : Supplemental Digital Content is available in the text.